Some Reflections on the Development of Our Regionalism, Starting From Gaspare Ambrosini’s Regional Model (Antologia di Diritto Pubblico, 2024)
The essay recognizes the fundamental role of Gaspare Ambrosini in the adoption of the regional model by the Italian Constitution of 1948. The author points out, however, that it is not certain that it was the weakness of this model itself, or the Constitutional reform of 2001, with its inclusion of “federal-inspired” characters, that caused the lackluster results of the regional experience as a whole, due rather to the way in which “Italian-style federalism” was implemented. A solution could be represented by the definitive transition of our system into a cooperative regionalism, which, however, is now threatened by the process of differentiated autonomy inspired by a model of asymmetric regionalism that the 2001 reform opened up also to ordinary regions, but which risks, if not implemented in a balanced way, to increase inequalities.
Keywords: form of State; federalism; regionalism; cooperative regionalism; asymmetric regionalism